Injustices of Shadow Information Technology in Creating Open Educational Resources - Mncube, Siphamandla; Legodi, Alex; Langa, Nozuko Precious (Universitas Negeri Makassar, 2024)
The emergence of open educational resources (OER) promotes open access which aims to widen information access as part of smart learning in higher education institutions. However, this has caused these institutions to rely on shadow information technology (SIT) for information access and service delivery, to the point where shadow IT principles contradict open education principles. When adopting and developing OER, academics, developers, and students often opt for different software or system software based on the usability and preferences of the system. Higher education institutions (HEIs), such as the University of South Africa (UNISA), are still conscious of the IT policy in terms of the appropriation of prescribed information and communication technology (ICT). However, this institution advocates for the adoption and development of OER, and social injustices when appropriating shadow IT are not yet addressed. To investigate the challenges and injustices encountered by academics in the utilization of shadow IT when creating OER, this study opted for a qualitative research approach. The data source was academics responsible for tuition and research. For data triangulation purposes, documents such as ICT policy, tuition policy, and comprehensive open distance e-learning (CODeL) policy were considered. To propose a model, this study utilized various concepts from different theories such as